2005
DOI: 10.1007/s10735-005-6061-x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the Neutral Amino Acid Transporter SNAT1 in the Developing Rat

Abstract: System A is a highly regulated, Na+-dependent transporter that accepts neutral amino acids containing short, polar side chains. System A plays an important role during rat development as decreased pup weights are observed in dams infused during gestation with a non-metabolizable System A substrate. Given the potential importance of SNAT1 during development in the rat brain, we examined whether SNAT1 would be present at an earlier gestation during organogenesis in multiple organs by immunohistochemistry and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Transport rates decreased along the proximodistal gradient of the fetal intestine, unlike those of adults that were greatest in the ileum (69). In rats, amino acid transport characteristic of systems X − AG and A are described in E17 embryos; intestinal mRNA transcripts for system A appear by E14, a full week before parturition (71,72). In piglets, transport of leucine initially detected in 7‐week‐old fetuses increased gradually in the last 2 weeks of gestation, along with the appearance of the proximodistal gradient of transport typical of adults (73).…”
Section: Proteinsmentioning
confidence: 99%
“…Transport rates decreased along the proximodistal gradient of the fetal intestine, unlike those of adults that were greatest in the ileum (69). In rats, amino acid transport characteristic of systems X − AG and A are described in E17 embryos; intestinal mRNA transcripts for system A appear by E14, a full week before parturition (71,72). In piglets, transport of leucine initially detected in 7‐week‐old fetuses increased gradually in the last 2 weeks of gestation, along with the appearance of the proximodistal gradient of transport typical of adults (73).…”
Section: Proteinsmentioning
confidence: 99%
“…Indeed, SNAT2 protein expression is thought to be critical at these stages since in vivo inhibition of system A is associated with suboptimal fetal growth (Cramer et al, 2002). This contrast with ontogenetic studies of SNAT1 (a system A isoform closely related to SNAT2), that display relatively constant levels of protein in brain throughout development (Weiss et al, 2003, 2005). Agreeing with the published protein data, we have determined that the mRNA levels for SNAT1 are also constant throughout development.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, increased System A transporter mRNA expression has been reported in the mouse placenta at E20, coinciding with the period of greatest fetal amino acid demand (Novak and Beveridge, 2000). Moreover, changes in the distribution of SNAT1 protein have been described during development and brain ontogenesis in the rat (Weiss et al, 2003, 2005). These data suggest that the quantity, activity and localization of a transporter may be critical for cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Our result revealed that LAT3 of the pancreas might not function at least after birth even under starved situation. Because several amino acid transporters such as SNAT1 46 and ASC1 47 have been identified at the protein level, the potential role of these molecules in the pancreas under the nutrientstarved condition should be further studied.…”
Section: Discussionmentioning
confidence: 99%